Difelikefalin in the Treatment of Chronic Kidney Disease-Associated Pruritus: A Systematic Review - Kamila Wala; Jacek C. Szepietowski (MDPI AG, 2022)
Chronic kidney disease-associated pruritus (CKD-aP) is a chronic condition that significantly reduces the quality of life of patients with end-stage renal disease. The etiology is not fully understood, but imbalance in the activity of the opioid pathways, including downregulation of the kappa-opioid receptor, may contribute to itching sensation. Difelikefalin is a selective, peripherally acting kappa-opioid receptor (KOR) agonist. Recently, difelikefalin has been approved as a first drug for the treatment of pruritus associated with chronic kidney disease (CKD) in adult hemodialysis patients. A systematic review of currently available clinical trials was performed to assess the efficacy and safety of difelikefalin in patients with uremic pruritus. A literature review was conducted in May 2022 based on the PRISMA 2020 guidelines. The analyzed clinical trials showed that difelikefalin was effective in reducing pruritus in patients as assessed by the Worst Itching Intensity Numerical Rating Scale. Improvement in quality of life assessed on the basis of the Skindex score and the 5-D itch scale was also noticed. The most commonly reported side effects were mild and included nausea, vomiting, dizziness, and diarrhea. Due to its proven efficacy and good safety profile, difelikefalin is a promising drug for the treatment of pruritus in patients with chronic kidney disease.